English as a vocation the 'Scrutiny' movement - Hilliard, Christopher (Oxford : Oxford University Press, 2012)
This text explores how a small circle of Cambridge literary critics turned into a movement that revolutionized the way English was taught and brought popular culture into classrooms.
Description based on online resource; title from PDF title page (viewed on July 16, 2012).
Includes bibliographical references and index.
Keywords: Criticism -- England -- Cambridge -- History -- 20th century; Criticism -- Study and teaching (Higher) -- England -- Cambridge -- History -- 20th century; Leavis, F. R. -- 1895-1978.; Scrutiny (Cambridge, England)